Legal Injustice in the Perspective of Pancasila: Various Recent Developments in Indonesia - Mutiah, Novia Isro’atul (Indonesian Journal of Pancasila and Global Constitutionalism, 2023)
Law enforcement in Indonesia has been regulated in the 1945 Constitution paragraph (1) of the 1945 Constitution where everyone is treated equally before the law without any distinction. As stated in the 5th Pancasila precept which reads: "Justice for all Indonesian people". But in reality the implementation of law enforcement in Indonesia is not going well. The law that should act decisively is now the opposite. In Indonesia, the law is used as a tool to act arbitrarily. An official, high-ranking official who has a lot of money will easily avoid legal disturbances even though the person has violated the law. And conversely for people who can not even get a severe punishment. This study aims to analyze the implementation of legal justice in the perspective of Pancasila in Indonesia as a basic framework in the state. This study uses a normative approach and literature study in which the author examines and compares various previous studies related to the topic of justice in the Pancasila perspective, as well as various related theories. This study finds and emphasizes that legal injustice in Indonesia is caused by the old paradigm of law enforcement officials, who still prioritize aspects of legal certainty and have not used aspects of justice and legal benefits. The legal apparatus associated with the court pays more attention to legal procedures, which they should prioritize existing legal justice.